2021
DOI: 10.3390/brainsci11070948
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Neurostimulation in Obsessive-Compulsive and Related Disorders: A Systematic Review

Abstract: Invasive and noninvasive neurostimulation therapies for obsessive-compulsive and related disorders (OCRD) were systematically reviewed with the aim of assessing clinical characteristics, methodologies, neuroanatomical substrates, and varied stimulation parameters. Previous reviews have focused on a narrow scope, statistical rather than clinical significance, grouped together heterogenous protocols, and proposed inconclusive outcomes and directions. Herein, a comprehensive and transdiagnostic evaluation of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 254 publications
(545 reference statements)
0
33
0
Order By: Relevance
“…Numerous studies have investigated the effects of tDCS in the treatment of refractory OCD. The targets selected were the same as those used for TMS, including pre-SMA/SMA, mPFC, DLPFC, and OFC ( 84 ).…”
Section: Methods Of Neuromodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the effects of tDCS in the treatment of refractory OCD. The targets selected were the same as those used for TMS, including pre-SMA/SMA, mPFC, DLPFC, and OFC ( 84 ).…”
Section: Methods Of Neuromodulationmentioning
confidence: 99%
“…Despite good response and remission rates of ALIC stimulation, its clinical usefulness is somewhat constrained by the high stimulation intensity required for beneficial results ( 84 , 119 ). Most clinical studies show effectiveness with ALIC stimulation only after extensive programming and with amplitudes of 5–10 V. Compared to DBS for movement disorders (Parkinson's disease, essential tremor, dystonia), amplitudes at this intensity necessitate frequent replacement of the implantable-pulse-generator.…”
Section: Methods Of Neuromodulationmentioning
confidence: 99%
“…Standard values have largely been adopted from movement disorder applications and may not be optimal for psychiatric conditions. Refinement of stimulation parameters, particularly the location, is a critical factor in achieving the best outcomes (Acevedo et al, 2021). Currently, the only established method is the Montgomery algorithm (Montgomery, 2010), which is not condition-specific, and deviations may be necessary when managing difficult cases, which comes with practical experience and cannot be described in a series of simple steps.…”
Section: Post-operativementioning
confidence: 99%
“…Furthermore, the Mental Health Act prohibits DBS for OCD in New South Wales, and the Northern Territory. In our recent systematic review (Acevedo et al, 2021), we identified several disparities in treatment approaches, which can confound patient outcomes, highlighting the need for standardization. Currently, there are no clinical guidelines or expert consensus outlining best practice in managing OCD DBS patients.…”
mentioning
confidence: 99%
“…103 A systematic review on clinical responses to several DBS targets in patients with TS showed fiber connectivity to be important in target selection because the effects of DBS on tics seem to occur through different networks at different stimulation sites. 104 Finally, an interesting case report described a patient with major depressive disorder who developed voltage-dependent coprolalia and tic-like movements along with changes in emotion, mood, and memory after DBS of bilateral ventral internal capsule and ventral striatum. 105…”
Section: Medicationmentioning
confidence: 99%